CLINICAL CASE OF COMPLEX TREATMENT OF PROGENIC BITE (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Progenic occlusion is a violation of the occlusion of the jaw, when the lower one protrudes more forward and overlaps the upper incisors. This causes the patient not only psychological problems, lack of proper aesthetics, possible discussions of the defect from the outside, but also affects health in general. Such patients have a combination of functional, morphological and aesthetic problems, the treatment of which requires orthodontic, orthopedic and surgical interventions.